American sensations : class, empire, and the production of popular culture - Streeby, Shelley, 1963- (American crossroads, 2002)
This innovative cultural history investigates an intriguing, thrilling, and often lurid assortment of sensational literature that was extremely popular in the United States in 1848--including dime novels, cheap story paper literature, and journalism for working-class Americans.